Increased OGA Expression and Activity in Leukocytes from Patients with Diabetes: Correlation with Inflammation Markers - Pagesy, Patrick; Tachet, Caroline; Mostefa-Kara, Ali; Larger, Etienne; Issad, Tarik (Experimental and Clinical Endocrinology & Diabetes, 2019)
O-linked-β-N-Acetylglucosaminylation (O-GlcNAcylation), a reversible post-translational modification involved in diabetic complications, is regulated by only two enzymes, O-linked N-acetylglucosamine transferase (OGT) and β-N-Acetylglucosaminidase (OGA). Increased OGA expression has been described previously in blood cells from patients with diabetes and was interpreted as an adaptative response to hyperglycemia-induced O-GlcNAcylation. OGA expression was thus proposed to have potential utility as a diagnostic marker. The present work was undertaken to determine whether determination of OGA enzymatic activity in blood cells could constitute a more rapidly accessible marker than OGA expression level measurements.Blood samples were obtained from patients with type 2 diabetes from the Department of Diabetology of the Cochin Hospital and healthy volunteers from the French blood Agency. OGA enzymatic activity and OGA mRNA expression levels were evaluated in leucocytes from patients with type 2 diabetes and from healthy donors.OGA activity was higher in leucocytes from patients with diabetes compared to control individuals. Surprisingly, OGA activity was not correlated hyperglycaemia markers (blood glucose, fructosamine, HbA1c) but was positively correlated with the inflammatory marker C-reactive protein. OGA mRNA levels were also increased in leucocytes from patients with diabetes and were correlated with mRNA coding for two pro-inflammatory proteins, TNFα and TxNIP.Therefore, OGA activity in leucocytes might be a more easily accessible biomarker than OGA expression levels. However, changes in OGA activity observed in patients with type 2 diabetes may reflect the inflammatory rather than the glycaemic status of these patients.
Keywords: O-GlcNAcylation; O-linked N-acetylglucosaminidase; O-linked N-acetylglucosamine transferase; hyperglycaemia; Diabetic complications; biomarkers